Cankarjeva metafora v vinjetnem obdobju - Čeh Steger, Jožica (Slavistična revija, 1997)
The vignette metaphor was derived from the author's dissonances in his subjective perception of reality and from the stylistic pluralism at the end of the 19th c. It was formed from the fundamentals of material beauty and ugliness, development of the basic conceptual metaphors, and the connection of related microstructural metaphors into larger, recognizably Cankarian metaphoric fields
Keywords: Cankar, Ivan, 1876-1918; Cankar, Ivan: Vinjete; literarne študije; metafora; metaforika; metaphor; prose; proza; Slovene literature; slovenska književnost